Metabolomic, Ionomic and Microbial Characterization of Olive Xylem Sap Reveals Differences According to Plant Age and Genotype - Manuel Anguita-Maeso; Carmen Haro; Miguel Montes-Borrego; Leonardo De La Fuente; Juan A. Navas-Cortés; Blanca B. Landa (Agronomy, 2021)
Vascular pathogens are the causal agents of main diseases threatening the health and growth of olive crops worldwide. The use of endophytic microorganisms represents a challenging and promising strategy for management of vascular diseases in olive. Although current research has been focused on analyzing the structure and diversity of the endophytic microbial communities inhabiting the olive xylem, the characterization of this ecological niche has been overlooked and to date remain unexplored, despite that the characterization of the xylem sap composition is essential to unravel the nutritional requirements of xylem-limited microorganisms. In this study, branches from plantlets and adult olive trees of cultivars Picual and Arbequina were selected to characterize the chemical and microbial composition of olive xylem sap extracted using a Scholander pressure chamber. Metabolome and ionome analyses of xylem sap were performed by proton nuclear magnetic resonance (NMR) spectroscopy-based and by inductively coupled plasma with optical emission spectroscopy (ICP-OES), respectively. Olive xylem sap metabolites included a higher relative percentage of sugars (54.35%), followed by alcohols (28.85%), amino acids (8.01%), organic acids (7.68%), and osmolytes (1.12%). Within each of these groups, the main metabolites in the olive xylem sap were mannitol, ethanol, glutamine, acetic acid, and trigonelline, whereas K and Cl− were the main element and inorganic anion, respectively. Metabolomic profile varied when comparing olive plant age and genotype. The levels of glucose, fructose, sucrose and mannitol, choline, B and PO43− were significantly higher in adult trees than in plantlets for both olive genotypes, whereas NO3− and Rb content showed the opposite behavior. On the other hand, levels of aspartic acid, phenylalanine, and Na were significantly higher in ‘Picual’ than in ‘Arbequina’, whereas Fe showed the opposite behavior, but only for adult trees. Microbiome composition identified Firmicutes (67%), Proteobacteria (22%) and Actinobacteriota (11%) as the main phyla, while at the genus level Anoxybacillus (52%), Cutibacterium (7%), Massilia (6%), and Pseudomonas (3%) were the most representative. Both non-supervised hierarchical clustering analysis and supervised PLS-DA analysis differentiated xylem sap chemical and microbial composition first, according to the age of the plant and then by the olive genotype. PLS-DA analysis revealed that B, ethanol, Fe, fructose, glucose, mannitol, sucrose, and Sr, and Anoxybacillus, Cutibacterium, and Bradyrhizobium were the most significant chemical compounds and bacterial genera, respectively, in the discrimination of adult olive trees and plantlets. Knowledge of the chemical composition of xylem sap will lead to a better understanding of the complex nutritional requirements of olive xylem-inhabiting microorganisms, including vascular pathogens and their potential antagonists, and may allow the better design of artificial growing media to improve the culturing of the olive microbiome.